Single-element 2D materials beyond graphene: Methods of epitaxial synthesis - Lozovoy, Kirill A.; Izhnin, Igor I.; Kokhanenko, Andrey P.; Dirko, Vladimir V.; Vinarskiy, Vladimir P.; Voytsekhovskiy, Alexander V.; Fitsych, Olena I.; Akimenko, Nataliya Yu (Nanotechnologies and nanomaterials: selected Papers from CCMR)
Today, two-dimensional materials are one of the key research topics for scientists around the world. Interest in 2D materials is not surprising because, thanks to their remarkable mechanical, thermal, electrical, magnetic, and optical properties, they promise to revolutionize electronics. The unique properties of graphene-like 2D materials give them the potential to create completely new types of devices for functional electronics, nanophotonics, and quantum technologies. This paper considers epitaxially grown two-dimensional allotropic modifications of single elements: graphene (C) and its analogs (transgraphenes) orophene (B), aluminene (Al), gallenene (Ga), indiene (In), thallene (Tl), silicene (Si), germanene (Ge), stanene (Sn), plumbene (Pb), phosphorene (P), arsenene (As), antimonene (Sb), bismuthene (Bi), selenene Se), and tellurene (Te). The emphasis is put on their structural parameters and technological modes in the method of molecular beam epitaxy, which ensure the production of high-quality defect-free single-lement two-dimensional structures of a large area for promising device applications.